PENGARUH DIMENSI BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN RUMAH TIPE 60 DI KOTA PALANGKA RAYA - Eka Kaharap, Mikhael (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This research aims to analyze the influence of the marketing mix on purchasing decisions for houses type 60 and above in the city of Palangka Raya. The focus of this research is to identify the factors that most influence consumer decisions in buying a house, which include price, product, location and promotion. The background to this research highlights the importance of housing as a basic human need as well as the increasing demand for housing in the city of Palangka Raya. With economic growth and increasing people’s incomes, the need for adequate and strategic housing becomes increasingly important. Various factors such as location, price and quality of living environment are the main considerations in home purchasing decisions. This research uses a quantitative approach with a survey method to collect data from respondents who have purchased houses of type 60 and above in Palangka Raya. The data collection technique involves distributing questionnaires to a number of randomly selected respondents. Data analysis was carried out using validity and reliability tests to ensure that the research instruments used were accurate and consistent. Next, path analysis using the SEM (Structural Equation Modeling) model was applied to test the relationship between the variables studied. The research results show that promotions through social media and freelance marketing are very effective in influencing home purchasing decisions. Social media allows developers to reach a wider audience at a lower cost, while freelance marketing provides flexibility and personalization in marketing approaches. Price was shown to be a major factor influencing purchasing decisions, indicating that consumers are highly sensitive to price changes and tend to choose homes that offer the best value. Meanwhile, product or home specifications do not show a significant influence on purchasing decisions, which may be due to the homogeneity of products in the housing market. The location of the house is a very important determining factor because consumers pay attention to the facilities available around the housing, such as access to transportation, schools, shopping centers and health facilities